Community Knowledge, Attitudes and Behaviors towards Obesity Prone to COVID-19 Infection - Ayu Saka Laksmita; Desak Putu Risky Vidika Apriyanthi; Ni Putu Widayanti (Disease Prevention and Public Health Journal, 2023)
Background: The COVID-19 pandemic is an infectious disease that has spread worldwide. Prevention of COVID-19 can be suppressed with a good level of knowledge and positive attitudes and behaviors. The community needs to play a role in breaking the chain of transmission of COVID-19 by implementing health protocols. The purpose of this study was to determine the relationship between the level of public knowledge about COVID-19 and the attitudes and behavior of the people of Denpasar City towards obesity, which are more susceptible to infection with COVID-19. Method: This type of non-experimental research with correlational design and cross-sectional design. The number of samples in this study was 400 respondents using simple random sampling. Data collection uses a questionnaire via WhatsApp with a google form. Results: The results showed that there was a relationship between public knowledge about COVID-19 and the attitudes and behavior of the people of Denpasar City towards obesity being more susceptible to infection with COVID-19 with p = 0.000 and r = 0.307 for attitudes and p = 0.000 and r = 0.408 for behavior. Conclusion: A strong correlation between the variable level of knowledge and attitudes and behavior and the direction of the relationship is positive, which means the better the level of knowledge, the better the attitude and behavior of the community to prevent contracting COVID-19.